Recurrent Non-islet Cell Tumor Hypoglycemia Secondary to Hepatocellular Carcinoma: Case Report and Literature Review - He, Dan; Gong, Hongpeng; Pan, Jie; Zhu, Fangchao; Jiang, Xiaofen; Su, Huang (Zeitschrift für Gastroenterologie, 2023)
Rationale Non-islet cell tumor hypoglycemia (NICTH) is a paraneoplastic syndrome caused by tumors other than insulinoma that is primarily due to excessive production of insulin-like growth factor-II (IGF-II). The prevalence of NICTH is likely underestimated because of a lack of clinical recognition.Patient Concerns A 41-year-old male with massive malignant liver tumors presented with recurrent severe hypoglycemia, weight loss, and liver cirrhosis.Diagnosis NICTH related to IGF-II produced by hepatocellular carcinoma was diagnosed based on clinical symptoms, biochemical tests, and elevated IGF-II/IGF-I ratio.Intervention Initial treatment with intravenous glucose and parenteral nutrition showed limited efficacy. Glucocorticoids and recombinant human growth hormone led to progressive improvement in blood glucose levels.Outcome Due to extensive tumor burden and liver failure, surgical resection was not feasible, and the patient ultimately succumbed to refractory hypoglycemia and passed away in two weeks.Lessons Early recognition and diagnosis of NICTH are crucial in patients with recurrent hypoglycemia and large tumors. Surgical resection is the preferred treatment option, but supportive care and pharmacological interventions, such as glucocorticoids and growth hormone, can help manage refractory hypoglycemia. Further research is needed to explore novel treatment options, including anti-IGF-I and -IGF-II neutralizing antibodies.
Keywords: case report; hepatocellular carcinoma; non-islet-cell tumor hypoglycemia; insulin-like growth factor; liver; metastasis